2014
DOI: 10.1002/lary.24729
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery for obstructive sleep apnea improve depression and sleepiness?

Abstract: Objectives/Hypothesis: To determine if surgical intervention for OSA (obstructive sleep apnea), particularly multilevel surgery, decreases depression and sleepiness.Study Design: Prospective cohort study. Methods: Chart and prospective outcome database review of patients who underwent surgery from August 2008 through November 2012. Patients were evaluated before and after surgery using the Epworth Sleepiness Scale (ESS), the Beck Depression Index (BDI), and overnight polysomnography.Results: Forty-four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…Sleep fragmentation and intermittent nocturnal hypoxia have been suggested as mechanisms through which OSA may contribute to depression in patients with OSA. 26 Oxygen saturation, intermittent hypoxia, and the arousal index were not associated with depression in the current study. It is possible that more severe intermittent hypoxia episodes, assessed by desaturations at 4%, may be more strongly associated with depression.…”
Section: Discussioncontrasting
confidence: 43%
“…Sleep fragmentation and intermittent nocturnal hypoxia have been suggested as mechanisms through which OSA may contribute to depression in patients with OSA. 26 Oxygen saturation, intermittent hypoxia, and the arousal index were not associated with depression in the current study. It is possible that more severe intermittent hypoxia episodes, assessed by desaturations at 4%, may be more strongly associated with depression.…”
Section: Discussioncontrasting
confidence: 43%
“…Asthma, diabetes, and obstructive sleep apnea have all been associated with depression. [24][25][26][27] Given these findings, we investigated the role of these comorbidities in the development of depression in CRS. We found that, even when controlling for these variables, CRS was still associated with higher BDI scores, which indicated independent effects of CRS on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale studies are essential to determine the deleterious effect of OSA on the incidence of depression and preventive effect of UPPP . Recently, Ishman et al reported that the Beck depression index decreased after surgery in patients with OSA . However, the study was based on only 44 patients, and its mean follow‐up period was very short: 115 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, several studies have shown that continuous positive airway pressure (CPAP) therapy in patients with OSA improved depression. 8,9 However, these findings are often conflicting, and in most studies the results could not be confirmed due to limited population samples. 6,7 Moreover, the impact of surgical treatment for OSA on depression has not been fully assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation